Costunolide Induces Autophagy and Apoptosis by Activating ROS/MAPK Signaling Pathways in Renal Cell Carcinoma - Fu, Dian; Wu, Ding; Cheng, Wen; Gao, Jianping; Zhang, Zhengyu; Ge, Jingping; Zhou, Wenquan; Xu, Zhenyu (Frontiers in Oncology, 2020)
Costunolide (Cos), a natural sesquiterpene compound that isolated from many herbal medicines, has exhibited potential anti-proliferative and pro-apoptotic activities in various types of cancers. However, the possible mechanisms of Cos-mediated tumor suppression are not clear. In this study, we further investigated the effects of Cos on several human renal cancer cell lines. Our results showed that Cos significantly inhibited human renal cancer cells growth via induction of apoptosis and autophagy in a concentration-dependent manner. Cos increased the Bax/Bcl-2 ratio, decreased the mitochondrial transmembrane potential, and triggered the release of cytochrome c from mitochondrial into the cytoplasm to activate caspase-9/-3, and cleaved PARP, resulting in the apoptosis of renal cancer cells. Meanwhile, autophagy induced by Cos was also demonstrated by the formation of GFP-LC3 puncta as well as the up-regulation of LC3B II and Beclin-1 proteins. Compared with Cos treatment alone, the autophagy inhibitor 3-MA or reactive oxygen species (ROS) antioxidants (NAC) can significantly inhibit apoptosis and autophagy. Moreover, Cos-induced apoptosis and autophagy was attenuated significantly with the treatment of NAC or JNK-specific inhibitor SP600125. Taken together, Cos can induce apoptosis and autophagy possibly via modulation of ROS/JNK signaling pathway in human renal cancer cells. Cos may be a promising agent for anticancer therapy against renal cancer.